Position control study of a bearingless multi-sector permanent magnet machine - Valente, Giorgio; Formentini, Andrea; Papini, Luca; Zanchetta, Pericle; Gerada, C. (2017)
Bearingless motors combine in the same structure the characteristics of conventional motors and magnetic bearings. Traditional bearingless machines rely on two independent sets of winding for suspension force and torque production, respectively. The proposed Multi-Sector Permanent Magnet (MSPM) motor exploits the spatial distribution of the multi-three-phase windings within the stator circumference in order to produce a controllable suspension force. Therefore, force and torque generation are embedded in the same winding setting. In this paper the force and torque generation principles are investigated and a mathematical model is presented considering the rotor displacement. A two Degree of freedom (DOF) position controller is designed taking into consideration the rotor overall dynamic system and a controller gains selection strategy is suggested. A simulation study of the bearingless system in different operating conditions is presented and the suspension force and torque produced are validated through Finite Element Analysis (FEA).